A systematic review of risk factors associated with the introduction of Mycobacterium avium spp. paratuberculosis (MAP) into dairy herds - Rangel, Saray J. (Can Vet J, 2015)
The objective of this study was to systematically collect and appraise the scientific evidence related to risk factors associated with the introduction of Mycobacterium avium spp. paratuberculosis (MAP) into a herd of cattle. An electronic search was conducted to collect relevant references addressing 2 specific questions: are i) purchasing/introduction of cattle into a herd, and ii) presence of wildlife or domestic animals, risk factors for the introduction of MAP into a herd? The screening was based on titles and abstracts and selected studies were fully analyzed. Seventeen manuscripts published between 1996 and 2011 were ultimately analyzed. Unit of interest was mainly the herd (n = 17). The specific description of the risk factors studied varied between studies. The principal study design was cross-sectional (n = 15). The review indicated that purchase/introduction of animals was an important risk factor and that the importance of wildlife or other domestic species as a mechanism for transmission into a cattle herd was not measurable.